PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI AKUNTANSI PADA SISTEM MANAJEMEN KOPERASI BRISYARIAH - Zaldy Suhatman (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2017)
Koperasi Karyawan BRISyariah was established in 2009 has several business units and members scattered throughout the work area of BRISyariah, For convenience accounting information system was made for Koperasi Karyawan  BRISyariah with web-based system using open source applications, applications used are PHP, Mysql And Apache. The author performs the design of Data Flow Diagram, database design, and also the interface design for cooperative members, administrators, cooperative staff to the chairman and manager, with this application is expected Koperasi Karaywan BRISyariah will be better again because reducing manual process like paper. In addition, there is also a reconstruction feature to compare data between Koperasi Karyawan BRISyariah with  human capital BRISyariah data.